American Orientalism and Vestiges of European Colonialism (Global Journal of Human-Social Science, 2018)
European Orientalism reiterates Western superiority over Oriental inferiority Yet American academia claims some indicative shift in the rite of narrating and representing the Other in literature film and other media The discourse of American Orientalism as it distances itself from the French frames through which the American writes the Orient tries to pay nearly much attention to the French Empire as they do to those Berber and Arab cultures of the Maghreb and North African landscapes 2 The version of Orientalism they formalize does not solely extend the constructions and presumptions of European Orientalism but it suggests a version through which Americans negotiate the presence of European colonialism 3 It is through this new American copyrighted vision that the discourse on the Other vacillates between the discourse of the savage and that of the civilized Orient 4as Porter claims in his reading of the imperialist discourse